Efficacy of a fungal decomposer in accelerating sugarcane trash decomposition and soil nutrient enrichment under semi-controlled conditions - Prashant Ravish; Smita Chaudhry (Discover Environment)
Abstract India produces more than 100 million tonnes of sugarcane annually, generating vast quantities of lignin-rich crop residue, nearly 70% of which are burned in-situ, contributing significantly to seasonal air pollution and nutrient depletion. While microbial decomposers have been adopted in rice–wheat systems, their potential for accelerating sugarcane trash degradation under conditions mimicking field environments remains underexplored. This study evaluated the efficacy of a PUSA decomposer consortium containing seven lignocellulolytic strains in enhancing the in-situ decomposition of sugarcane trash under semi controlled pot-scale glasshouse conditions simulating field dynamics. A 45-day decomposition trial was conducted via a completely randomized design with three treatments—untreated control (T₁), water plus fermented substrate (T₂), and PUSA decomposer plus substrate (T₃), sampled at Days 0, 15, 30, and 45. Under T₃, soil microbial biomass carbon (SMBC) increased by 47%, available phosphorus increased by 28.7%, potassium increased by 15.1%, and nitrogen increased by 8.7% over the 45-day period. The lignin content decreased by 27.5%, whereas the lignin-to-cellulose (L/C) ratio remained stable at 0.20, indicating the proportionate degradation of structural residues. The soil pH and EC remained within agronomic thresholds. These findings demonstrate the potential of the PUSA decomposer to accelerate lignocellulose breakdown, improve soil fertility, and offer a viable alternative to open burning. Field-scale validation under diverse agroclimatic conditions is recommended to support large-scale adoption.